Exploring positive psychology intervention and mindfulness-based intervention in nature: impact on well-being of school students in India - Chhajer, Raina; Hira, Nainika (Frontiers in Public Health, 2024)
Enhancing the well-being of urban school students is a growing challenge. The online mode of teaching during and post-pandemic era has increased students' daily screen time. As they spend more time indoors, they tend to disconnect from nature even more, adversely impacting their well-being. This study aims to design and execute two well-being interventions -a positive psychology intervention (PPI) and a mindfulness-based intervention (MBI) in natural settings for urban school students in India. 180 participants (aged 17-20) from a senior secondary school were randomly assigned to three groups: PPI, MBI, and a control group (CTR). Participants self-reported their levels of well-being, gratitude, inclusion of nature in self, sense of connectedness, resilience, awareness, perceived stress, positive and negative emotions using a survey questionnaire at two times -pre and post interventions. Repeated measures analysis of variance (ANOVA) was employed across time and groups, and post-hoc analyses for group differences were carried out through the Bonferroni test. Results indicate that both PPI and MBI interventions, when executed in natural settings, enhance student wellbeing, gratitude, inclusion of nature in self, sense of connectedness, resilience, awareness, and positive emotions and decrease levels of perceived stress, and negative emotions. The study provides valuable insights for school authorities, policymakers, and urban planners to include natural settings in school premises and offer well-being interventions for students to connect with nature consciously.